Probing the Defect Induced Magnetocaloric Effect on Ferrite/Graphene Functional Nanocomposites and Their Magnetic Hyperthermia - Casagrande-Denardin, J; Melo-Freire, R (American Chemical Society, 2019)
Recently, the development of an alternative magnetic refrigerant for the conventional fossil fuels attracts the researchers. We discussed the structural defect-induced magnetocaloric effect (MCE) in Ni0.3Zn0.7Fe2O4/graphene (NZF/G) nanocomposites for the first time. Single-phase spinel ferrite nanocomposites with an average size of 7-11.4 nm were achieved by using the microwave-assisted coprecipitation method. The effect of graphene loading on the structural and magnetism of NZF/G nanocomposites was elaborated. Raman analysis proved that the interface interaction between NZF and graphene yielded different densities of structural defects. In view of magnetism, superparamagnetic NZF nanoparticles showed a magnetic entropy change (-Î"SMmax) of-0.678 Jkg-1 K-1 at 135 K, whereas the NZF/G nanocomposites exhibited superior-Î"SMmax at cryogenic temperatures and the defect-induced MCE change was indeed similar to the ID/IG intensity ratio. The nanocomposites exhibited different magnetic orderings between 5 and 295 K, and it was varying for ID/IG, 1.83 > 1.68 > 1.57 as antiferromagnetic (AFM) > AFM/ferrimagnetic (FiM) > FiM, respectively. Till now, NZF/G nanocomposites showed an inverse MCE of 4.378 Jkg-1 K-1 at 35 K and a refrigerant capacity of 88 Jkg-1 for 40 kOe, which was greater than the ferrites reported so far. Finally, MCE and magnetic hyperthermia were correlated at ambient conditions. These results pave the way for ferrite/graphene nanocomposites for cooling applications. Copyright © 2019 American Chemical Society.